If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n(5n + -3) = 0 Reorder the terms: -5n(-3 + 5n) = 0 (-3 * -5n + 5n * -5n) = 0 (15n + -25n2) = 0 Solving 15n + -25n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '5n'. 5n(3 + -5n) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(3 + -5n)' equal to zero and attempt to solve: Simplifying 3 + -5n = 0 Solving 3 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5n = 0 + -3 -5n = 0 + -3 Combine like terms: 0 + -3 = -3 -5n = -3 Divide each side by '-5'. n = 0.6 Simplifying n = 0.6Solution
n = {0, 0.6}
| -1+8x=-4x+5 | | 8x+5y=-105 | | 6t+3=8t+11 | | -10x^7-5x^3+4x-22=0 | | 1+6n=4n+3 | | 8z+4-2z=58 | | 2n=34 | | 36a-2=36+8 | | 512.3852=2*3.14r^2+2*3.14*r*15.8 | | 8z+42z=58 | | n+5/9=1/6 | | 18y^2+12= | | 18k=108 | | 5a+5b+2a+3b= | | 11t-9t=10 | | (9x-8)(3x+9)=0 | | 10y-9=17y+33 | | j-1=5 | | 4z-2=z+4 | | 7x-9=9-2x | | 5d=42-2d | | -3.2y+15=-2.4-10 | | 4s+3=5s | | 3(4k-2)=12k-6 | | d+20=-12-d | | 2x^2+10x-35=0 | | -10e+15=90-30e | | 13+12h=7h-2+10 | | 3(-7z-6)+17=-17 | | 16y-2y-3=o | | p(x+q)=rx | | 4u-5=2+5u |